Experienced justice: gender, judging and appellate courts - Hilly, LE (2014)
The under-representation of women in the senior appellate judiciary in common law jurisdictions remains an enduring problem. Much has been written about the lack of women’s participation in the judiciary and what strategies, if any, should be undertaken in order to resolve this persistent problem. However, this thesis takes a step back to ask a broader question: what impact does gender diversity have upon judicial decision making in appellate courts? It seeks to answer this question by engaging feminist standpoint theory to assess the experiences of men and women judges from three common law jurisdictions: England, South Africa and Australia. Through a series of interviews conducted with members of the senior judiciary in these jurisdictions in 2012 and 2013, this thesis explores the extent that interviewees consider that gendered experiences impact upon their own judging, and judging within the dynamics of collegiate appellate courts. This thesis concludes that while it is not possible to pinpoint one particular ‘contribution’ or ‘impact’ that gendered experiences have upon judging, it is nonetheless generally considered by those interviewed to be an important part of the judicial decision making process in several subtle, yet important, ways. Because of the considerable role that diverse gendered experiences play in judicial decision making, appointments processes should be sensitised to the need for diversity of experience and alive to the danger of ostensibly neutral appointment criteria devaluing diverse experiences, particularly the experiences of women in the law.